2022
DOI: 10.3390/nu14061199
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Effects of Multiple Doses of a Medium Chain Triglycerides Enriched Ketogenic Formula in Healthy Men under the Ketogenic Diet: A Randomized, Double-Blinded, Placebo-Controlled Study

Abstract: Ketogenic diets, which are carbohydrate-restricted high-fat diets, may have therapeutic effects on various diseases, including cancer. However, ketogenic diets are often not standardized and, therefore, results are difficult to interpret. We previously investigated the usefulness of ketogenic diets in cancer therapy, where ketogenic formulas (KF) were used as supplements to enhance blood ketone bodies; however, the amount of KF was determined empirically with reference to blood ketone bodies levels. Here, to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The ketogenesis of MCT is suppressed by consuming carbohydrate with MCT ( 35 ). Although we have previously demonstrated that the ketogenic formula increased blood ketone bodies under conditions of a ketogenic diet ( 36 ), further studies are required to investigate how much the ketogenesis of MCT decreases depending on the amount of carbohydrates ingested at the same time.…”
Section: Discussionmentioning
confidence: 98%
“…The ketogenesis of MCT is suppressed by consuming carbohydrate with MCT ( 35 ). Although we have previously demonstrated that the ketogenic formula increased blood ketone bodies under conditions of a ketogenic diet ( 36 ), further studies are required to investigate how much the ketogenesis of MCT decreases depending on the amount of carbohydrates ingested at the same time.…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to the cited results, another KD trial found decreased UA levels on week 24 of intervention 39 . Most of these studies noted a transient hyperuricemia which is primarily present in the early course of the KD initiation; such as the significant serum UA elevation observed in healthy non-obese men 5 days following KD 40 . The hypothesis for the elevated serum UA would be that in KD, when glucose availability drops, other metabolic processes such as ketogenesis rise to compensate for the energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Although a ketogenic diet has been introduced as an effective means of weight loss, the mechanisms underlying its ameliorative effects have not yet been fully explored. Previous studies have demonstrated the potential of the ketogenic diet (KD) to modify the diversity and species composition of the gut microbiota in individuals with various health conditions, including obesity [26], type 2 diabetes [42], cancer [43], epilepsy [44][45][46], and cognitive impairment [47,48], and Alzheimer's disease [49], as well as healthy individuals [50]. However, the majority of these investigations have predominantly centered on genuslevel discussions of microbial composition, often overlooking the examination of the correlation between individual microbial species and their functional alterations in response to obesity and dietary patterns.…”
Section: Discussionmentioning
confidence: 99%